Analisis Strategi dan Dampak Implementasi Inovasi Produk Terhadap Voleme Penjualan UMKM Buket di Kabupaten Jombang - Intan Nur Laili, Intan Nur Laili; Tri Atmojo, Cahyo; Tri Wahono, Heru Totok (Universitas Nusantara PGRI Kediri, 2024)
The aim of this research is to reveal product innovation strategies and the impact of implementation on Bouquet MSMEs in Jombang Regency. By uncovering the phenomenon, we will be able to find out what product innovations are being implemented and what the impact of changes will be on the sales volume of Bouquet MSMEs in Jombang Regency. In uncovering this phenomenon, researchers used a qualitative descriptive approach with various data collection methods including using interviews, observation and documentation methods. The informants in this research were bouquet entrepreneurs including Lail Craft, Mita-Made Bouquets, and Livia Felt Bouqet. The researcher carries out data analysis starting with the researcher starting by carrying out the data collection process using the chosen method, then the researcher carries out data reduction based on the results of data collection that have been received from key informants and supporting informants in the research, and after that in the third process the researcher presents the data through tabulation, and in the final process, the researcher draws conclusions. To test the validity, the researcher used source triangulation and method triangulation. The research results that the researchers can reveal include the researchers making changes to current strategies according to current developments in the era of the 2024 generation. The product innovation strategy carried out on bouquet products includes changing the design of the bouquet and also making a bouquet that is more flexible to suit customer desires. The designs are not just flower bouquets but more variations of dolls carrying snacks or cartoon characters carrying money. This has an impact on sales volumes increasing compared to before.